2009
DOI: 10.1111/j.1574-6968.2009.01512.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of plasmid-mediated resistance to tetracycline in pathogenic bacteria from fish and aquaculture environments

Abstract: The transferability of a large plasmid that harbors a tetracycline resistance gene tet(S), to fish and human pathogens was assessed using electrotransformation and conjugation. The plasmid, originally isolated from fish intestinal Lactococcus lactis ssp. lactis KYA-7, has potent antagonistic activity against the selected recipients (Lactococcus garvieae and Listeria monocytogenes), preventing conjugation. Therefore the tetracycline resistance determinant was transferred via electroporation to L. garvieae. A tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 44 publications
4
40
0
3
Order By: Relevance
“…Guglielmetti et al (2009) demonstrated the transfer of tet(S) gene by conjugation from Lactococcus garvieae (fish pathogen) to the human pathogen L. monocytogenes, indicating the possibility of the transfer of tet genes from lactococci to human bacteria. The analysis of the presence of plasmids and the Tn916 transposon in six Tet R L. lactis strains supported these assumptions because most of the tet genes investigated in this study were also identified on mobile elements.…”
Section: Discussionmentioning
confidence: 97%
“…Guglielmetti et al (2009) demonstrated the transfer of tet(S) gene by conjugation from Lactococcus garvieae (fish pathogen) to the human pathogen L. monocytogenes, indicating the possibility of the transfer of tet genes from lactococci to human bacteria. The analysis of the presence of plasmids and the Tn916 transposon in six Tet R L. lactis strains supported these assumptions because most of the tet genes investigated in this study were also identified on mobile elements.…”
Section: Discussionmentioning
confidence: 97%
“…This was also affirmed by the fisheries officers interviewed. Tetracycline is known to be one of the most commonly used antibiotics in fish farms especially in hatcheries [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic-resistant bacteria may represent a potential threat to human health due to direct transmission through the food chain (Duran and Marshall, 2005) or by transferring the acquired antimicrobial resistance to human pathogens by mobile genetic elements (Angulo, 2000;Serrano, 2005;Guglielmetti et al, 2009). Although several investigations have been conducted in different countries regarding antibiotic resistance in Vibrio spp.…”
Section: Introductionmentioning
confidence: 99%